Pengaruh Akuntabilitas Pengelolaan Keuangan Alokasi Dana Desa, Kebijakan Desa, Dan Kelembagaan Desa terhadap Pemberdayaan Masyarakat ( Studi Kasus di Desa Pundungsari Kecamatan Tempursari Kabupaten Lumajang) - Rina Indrawati Syafi’i; Abdul Wahid Mahsuni; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThis research to determine the accountability of village fund allocationmanagement, village policy, and village institutions towards communityempowerment. Methods of data collection in this study using questionnairemethod. In this research the sampling technique using purposive sampling. Theresearch population used was 1122 family head of Pundungsari Village,Tempursari Sub-district, Lumajang Regency using slovin formula.The results of this study indicate that the management of ADD must actually beimplemented through the village finance section that is used for communityempowerment but the Pundungsari villagers do not yet know fully thesocialization of the draft ADD budget undertaken by the village administration.The village policy established by the center is directly accepted and followed bythe Pundungsari Village apparatus well in carrying out the communityempowerment of Pundungsari Village. As well as existing policies at times maychange in accordance with what will be implemented in their government andPundungsari village institutions have not played an active role in villageactivities such as the activities of PKK the guidance of the task force. Andshould the village institutions more active role in supporting communityempowerment.Keywords: ADD accountability, community empowerment, village policy, villageinstitutions